Gender Roles and Social Themes in the Grade Ten English Textbook: A Critical Discourse Analysis - Chapain, Dipendra (NPRC Journal of Multidisciplinary Research, 2025)
Textbooks play a crucial role in shaping students' perspectives, particularly in language education, where they serve as a primary medium of cultural and social transmission. This study critically examines the Grade Ten Compulsory English Textbook used in Nepal, focusing on gender representation and social orientation. Using Penny Ur’s (2009) framework for textbook analysis and Fairclough’s (1989) three-dimensional model of discourse analysis, this study explores how males and females are portrayed in dialogues, images, and activities, as well as how social classes and occupations are represented in the textbook. The findings reveal a mixed portrayal of gender, where males dominate certain sections while females have limited representation in leadership roles. The analysis also indicates a lack of diversity in occupational roles and underrepresentation of Nepalese social and cultural realities, highlighting a preference for Western ideals over local perspectives. These disparities raise concerns about the implicit messages students receive regarding gender roles and societal structures. The study concludes with recommendations for a more inclusive and balanced representation of gender and social diversity in English language textbooks, ensuring a fair and equitable learning experience for all students.